2020
DOI: 10.1002/admi.202001442
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Superhydrophobic Surfaces within Various Condensation Environments: A Review

Abstract: Steam condensation is omnipresent, and inevitable in many industrial processes. A classic example is seen within condensers that are used to liquify various gasses. In consequence, water‐vapor is eventually deposited upon the exterior of heat pipes that passively cool the gas to form a thin film of liquid. This macroscopic film is responsible for the degradation of heat transfer efficiencies. Liquid repellent surfaces can microscopically manipulate the hydrodynamics of formulating condensate to transition towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 137 publications
(179 reference statements)
0
10
0
Order By: Relevance
“…Condensation is an efficient mass‐transfer process observed in nature and is essential to many industrial applications such as thermoelectric and nuclear power generation, [ 1 ] water harvesting systems, [ 2 , 3 , 4 , 5 , 6 ] heat exchangers, [ 7 , 8 ] and desalination plants. [ 9 , 10 ] Condensation involves the nucleation of droplets on a surface that can lead to significant heat and mass transfer improvement depending on the droplet dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Condensation is an efficient mass‐transfer process observed in nature and is essential to many industrial applications such as thermoelectric and nuclear power generation, [ 1 ] water harvesting systems, [ 2 , 3 , 4 , 5 , 6 ] heat exchangers, [ 7 , 8 ] and desalination plants. [ 9 , 10 ] Condensation involves the nucleation of droplets on a surface that can lead to significant heat and mass transfer improvement depending on the droplet dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Active air plastron thus could help restore the superhydrophobicity in situ against dynamic environments. Also, previous studies revealed that condensation could influence the non-wetting feature of passive superhydrophobic surfaces, 41,42 the strategy developed here would be effective to reduce this effect.…”
Section: Resultsmentioning
confidence: 86%
“…The pitcher plant, where insects slip into the pitcher and are then digested for food, served as the inspiration for the slippery surfaces depicted in Figure 12 [ 264 ]. Figure 12 shows the microscopic and macroscopic grooves over the surface, which are separated by ridges, providing hindrance to the lateral spread of water by enhancing the radial spread towards creating slippery surfaces [ 265 , 266 ]. A new class of liquid-repellent surfaces with self-cleaning capabilities can be created by the surface morphology of pitcher plants along with the microscopic and macroscopic grooves [ 267 ].…”
Section: Biomimetic Surfaces Inspired By Plantsmentioning
confidence: 99%